Generalized model of an axial dynamic generator - PUCH, Andrzej (Archives of Acoustics, 1978)
This paper present a model of the theoretical acoustic system of a dynamic axial generator with a horn and pressure chamber common to all channels of the stator. The model has been developed on the basis of electroacoustic analogies. This permits formulation of the wave phenomena encountered in the acoustic system of the generator. Experimental investigations have shown that the model is correct within the range of conditions assumed during its formation. Postulates have also been formulated which, when satisfied, will permit the optimal working of the generator over a wider frequency range.